Radio frequency based detection of specific and nonspecific protein interaction - Annesha Mazumder; Arunangshu Biswas; Tapan K. Sau; Prabhakar Bhimalapuram; Azeemuddin Syed (Frontiers in Sensors, 2025)
IntroductionProtein detection plays a crucial role in diagnostics and numerous studies. Available protein detection techniques often involve time-consuming and complicated procedures. This report presents a Radio frequency (RF)-based rapid, label-free technique that can be used for differentiation between specific and non-specific binding.MethodsThe utility of the RF-based technique is demonstrated by taking biotin-streptavidin specific interaction as the model system along with other nonspecific proteins. The study involves the use of an interdigitated capacitor-based RF sensor that differentiates the variation in the resonance frequency of the analytes with specific or nonspecific protein binding. The protein binding event is carried out in the presence of gold nanoparticles, which provide the surface for molecular binding and signal amplification.Results and discussionThe specific binding of biotin-streptavidin is characterized by a constant resonance frequency which does not vary with time or after use of the wash buffer. Contrarily, the resonance frequency shows significant variation in the case of the non-specific interactions like biotin-cytochrome C and biotin-lysozyme. A simulation-based analysis performed using High Frequency Structure Simulator (HFSS) corroborates the finding. The invariant resonance frequency response of the specific protein binding can be utilized as the basis of specific protein detection using RF sensing. The facile RF sensor shows excellent potential as a rapid, reusable, and versatile platform that can be performed remotely without sophisticated laboratory arrangements for protein detection.